The Effect of Iso and Shutter Speed Variations On the Quality of Dawn Light Astrophotography - Andri, Sela Septi; Abdul Ghofur; Nuril Fathoni Hamas; M. Zaidul Kirom (Universitas Islam Negeri Mataram, 2024)
The setting of the exsposure is one of the important factors in producing high-quality dawn images. The ISO and shutter speed settings on Android phones have provided significant support for astrophotography, especially in dawn imagery. This study aims to analyze the effect of variations in ISO values (800, 1600, and Auto) and shutter speed (8 seconds, 10 seconds, and Auto) on the quality of dawn images through comparison. This study is a comparative quantitative study that aims to measure the influence of independent variables, namely ISO values and shutter speed, on dependent variables, namely the quality of dawn imagery in astrophotography. Data analysis was carried out using AstroimageJ software to measure the effect of ISO value setting and shutter speed on dawn image quality. Based on the results of the analysis, it can be concluded that the ISO and shutter speed value settings have a significant influence on the quality of dawn images. then ISO and shutter speed settings in Auto mode are more ideally used, because this mode can adjust to the existing lighting conditions.